NANOENKAPSULASI EKSTRAK KUNYIT DENGAN KITOSAN DAN SODIUM-TRIPOLIFOSFAT SEBAGAI ADITIF PAKAN DALAM UPAYA PERBAIKAN KECERNAAN, KINERJA DAN KUALITAS DAGING AYAM BROILER - , Ir. Sundari, MP, Prof. Dr. Ir. Zuprizal, DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to look for the formula and the best level of nanocapsule (nanoparticle = NP) turmeric extract on digestibility, performance and meat quality of broiler chickens. The study composed of 3 stages, namely: 1). Looking for the best formula of 12 combinations with three factors as the following: 2 turmeric extract concentrations (0.01 and 0.02%) , 3 chitosan concentrations (0.01, 0.02, and 0.03%) , and 2 STPP concentrations (0.01 and 0.02%), 2). Looking for optimal level of NP on nutrient digestibility and metabolizable energy by total collection method of feed and excreta from 120 broiler chickens which were randomly divided into 20 treatments of 6 birds each. 3). Looking for the best level of NP in the diet on intestinal performance, production performance and meat quality of broiler chickens. The third stage had used 120 male broiler chickens of Lohmann strain, which were randomly divided into 10 treatments with 3 replications and 4 birds per unit cage. Data were analyzed by one-way ANOVA, if there were any significant differences then followed by Duncanâs test. The results obtained from stage 1 was that the best formula to be E nanocapsule having proportion values between turmeric extract to chitosan and to STPP to be 2%:2%:1% w/v with the proportion values between successive solvent ethanol to acetate buffer of pH 4 and to distilled water to be 1:8:1 for 1000 ml, it had the antibacterial activity on E. coli with 5 to 10 mm inhibitory zone diameter. On stage 2 it was seen that the best result significantly different (P<0.05) was found from adding nanocapsule at the level of 0.1% giving true metabolizable energy (TME) value of 3370.66 kcal/kg, and at the level of 0.4% produced nutrient digestibilities (dry matter as much 73%, organic matter 76%, crude protein 67%, crude fat 78% and crude fiber 25%). On stage 3 it was found out that optimal level was the addition of nanocapsule 0.2% which produced FCR value of 1.71 although not different statiatically with the other levels (P>0.05). At level of 0.4% produced best values (P<0.05) of mucosa thickness 979.70 Âµm which was equivalent to the use of 50 ppm bacitracin, meat protein of 22.57%, high water-holding capacity of 21.36%, rich EPA fatty acids of 1.38% and DHA of 2.08%. It was concluded that nanocapsule turmeric extract of E formula had antibacterial activity, and the use of 0.4% in the diets could replace the use 50 ppm bacitracin and could improve intestinal performance, nutrient digestibilities, production performance and meat quality of broiler chickens